Solve for X
X: E^(2x)-(5E^x)-6=0
You don't have to solve it for me, but if I could get a hint it would help. Thanks ahead of time.
Thanks BAdhi.
So I substitute and use the quadratic equation. And I get say Y=6 or Y=-1. Then I say E^x=6 or E^x=-1. Do I now say, Log e (6)=x, or log e (-1)=x
And because log e (-1)=x, I can say that E must equal in this case=-1, and x must be an odd integer?
So, X=all odd integers, or X=log e (6)? Depending on which solution for E you use? Is this correct, and if so how do I properly write this answer?